HUBUNGAN RESILIENSI DENGAN TINGKAT KECEMASAN PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI - Fitri, Indri Nuraeni; Agustiyowati, Tri Hapsari Retno; Meilianingsih, Lia; Sukarni, Sukarni; Waluya, Nandang Ahmad (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2024)
In 2020, the prevalence of breast cancer in Indonesia reached 65,858 cases (16.6%) with 22,430 deaths (9.6%) from 396,914 cancer cases. Breast cancer treatment therapy often involves chemotherapy, which can have psychological side effects, notably anxiety. Anxiety can occur due to a person’s lack of ability to adapt when facing difficulties, also known as resilience. The study aimed to determine the relationship between resilience and anxiety levels in breast cancer patients undergoing chemotherapy at Al-Ihsan Hospital, West Java Province. This research was a descriptive correlational research using a cross-sectional approach. Sampling was using a purposive sampling technique, resulting in a total of 84 respondents. The measuring instruments used were Connor Davidson-Resilience Scale (CD-RISC) 25 and Zung Self-Rating Anxiety Scale (ZSAS).The results showed that respondents had moderate resilience with an average score of 70.51, and moderate anxiety with an average score of 39.00. The results of the Spearman Rho statistical test indicated a relationship between resilience and anxiety levels in breast cancer patients undergoing chemotherapy at Al-Ihsan Hospital, West Java Province, with a p-value of 0.000 (p<α) and a calculated r-value of -0.520, indicating a strong and negative relationship. This suggests that the higher resilience in breast cancer patients undergoing chemotherapy, the lower level of anxiety experienced. Providing comprehensive nursing care is especially necessary for breast cancer patients who undergo chemotherapy for less than one year. Social support from family and medical personnel can help increase resilience and reduce the anxiety levels of breast cancer patients.